Simbol Religius dalam novel Hati Suhita (Studi Semiotika Perspektif Charles Sanders Pierce) - Reni Rahmawati; Siti Raudhatul Jannah (Icon: Islamic Communication and Contemporary Media Studies, 2022)
This article aims to find out the religious symbols in the novel Hati Suhita by Khilma Anis. This research uses a qualitative research type with a descriptive approach. This research method was carried out by selecting and sorting out several icon quotes, indices, and religious symbols for later analysis with Charles Sanders Pierce's semiotic theory with the aim of knowing the form of signs, functions and meanings in the novel Hati Suhita. The researcher also made observations, documentation, adding supporting data with literature studies and checking the validity of the data using source triagulation. The results of this study indicate that several religious symbols in Charles' semiotic aspect include (1) icon categorization found 30 quotes (2) index categorization found 22 quotes (3) symbol categorization found 23 quotes. The symbols found include symbols of children's obedience to their parents, wife's obedience to her husband, obedience to Allah, patience, gratitude, guardian pilgrimage, tabarrukan, santri day, pesantren, orphans, deliberation, Haul Masyayikh, takdzim, 'alim and khadziq. , muthola'ah, and tirakat.